Dynamics of Development of the USA, Canada and UK Financial Markets in the Display of Stock Indices of their Banking Institutions - Baranova, V.; Viadrova, I.; Lyashenko, V. (IJAAFMR, 2022)
The stock market and the banking segment of the economy are key elements of the financial system. These key elements of the financial system are aimed at the effective functioning of both individual business entities and the country as a whole. Therefore, an important task of the study is to analyze the dynamics of development of both the stock mark et and the banking segment of the economy. At the same time, one of the points for achieving such efficiency is the coordinated interaction between the stock market and the banking segment of the overall financial system. Ultimately, such interaction contributes to the sustainable development of the economy and the country as a whole. Sustainable interaction between the stock market and the banking segment of the economy is achieved using various tools. Then, in order to analyze the interaction between the stock market and the banking sector of the economy, a study should be carried out for the relevant tools for analyzing such segments of the financial market. At the same time, the effectiveness of such interaction can be assessed on the basis of an analysis of the dynamics of the relevant stock indices. Among such stock indexes, we have chosen indices of banking institutions, which reflect the activities of banks in each individual country. Such indices reflect the development of the respective business entities, as they take into account the value of such companies. These stock indices make it possible to consider the dynamics of the functioning of the banking sector of the economy in conjunction with the development of the relevant stock markets. Among such countries, we consider USA, Canada and UK. To carry out the corresponding analysis, we use the ideology of wavelets. As an analysis tool, we chose the wavelet coherence method. This choice of instruments for our study allows for a comparative analysis of the data. This makes it possible to assess the dynamics of development of the relevant business entities, to give a mutual assessment of such development. The work presents many graphs and diagrams. This allows you to understand the logic of the study and better interpret the results.
Keywords: stock market; wavelet analysis